Management of Recurrent Pterygium with Severe Symblepharon Using Mitomycin C, Double Amniotic Membrane Transplantation, Cryopreserved Limbal Allograft, and a Conjunctival Flap - Monden Y; Nagashima C; Yokote N; Hotokezaka F; Maeda S; Sasaki K; Yamakawa R; Yoshida S (International Medical Case Reports Journal, 2020)
Yu Monden, Chikako Nagashima, Noriko Yokote, Fumi Hotokezaka, Satoshi Maeda, Kensuke Sasaki, Ryoji Yamakawa, Shigeo Yoshida Department of Ophthalmology, Kurume University School of Medicine, Fukuoka, JapanCorrespondence: Yu MondenDepartment of Ophthalmology, Kurume University School of Medicine, 67 Asahi-machi, Kurume, Fukuoka 830 0011, JapanTel +81-942-317574Fax +81-942-370324Email you@med.kurume-u.ac.jpPurpose: The aim of this study was to evaluate the clinical outcomes of management of recurrent pterygium with severe symblepharon using mitomycin C, double amniotic membrane transplantation, cryopreserved limbal allograft, and a conjunctival flap.Patients and Methods: This retrospective case series included 10 eyes of 10 patients with recurrent pterygium with severe symblepharon. Eight patients have diplopia in primary gaze. All patients underwent pterygium excision, application of mitomycin C (MMC), double amniotic membrane transplantation (AMT), cryopreserved limbal allograft (CLA) transplantation, and placement of a conjunctival flap. Outcome measures were visual acuity, astigmatism, and recurrence. Recurrence was defined as the presence of fibrovascular proliferative tissue crossing the limbus.Results: The patients’ mean age was 73.8 years. The mean follow-up period was 3.0 years. The mean preoperative and postoperative best-corrected visual acuities (logMAR conversion) were 0.43 and 0.30, respectively. The mean preoperative and postoperative astigmatism were – 3.89 diopters and – 1.54 diopters, respectively, and there was a significant difference. No recurrence occurred in any of the eyes. Symblepharon was released in all eyes. Diplopia in primary gaze was resolved in all eyes.Conclusion: Management of recurrent pterygium with severe symblepharon using MMC, double AMT, CLA, and a conjunctival flap was an effective treatment.Keywords: pterygium, symblepharon, limbal allograft, amnion, mitomycin C